Depurated fish as an alternative reference for field-based biomarker monitoring - Webb, Diane; Gagnon, Marthe Monique (Springer Netherlands, 2013)
The whole of the Swan-Canning Estuary, in the south-west of Australia, is impacted by human activity, and the selection of a local reference site to assess the impact of environmental contamination on the health of biota is not possible. To determine whether fish depurated under laboratory conditions could be used as an alternative to a reference site; adult black bream (Acanthopagrus butcheri) were collected from the estuary and maintained in clean water (S24) for 3 months. A suite of biomarkers of fish health were assessed, and the results were compared with field-captured black bream from three sites within the estuary (Ascot, Claisebrook, and Riverton). Comparisons of a subset of biomarkers were also made between hatchery-bred juvenile fish and the depurated fish. Biomarker levels were up to 3.8 times higher in field captured fish compared with depurated fish, while DNA integrity was lower. EROD activity was comparable in the hatchery-bred black bream to the depurated fish while s-SDH levels were two times higher in the hatchery fish. From the results obtained, field-captured black bream depurated for 3 months are suitable to determine reference/baseline levels for biomarker of health studies in estuarine environments.